The founding of Mauritian endemic coffee trees by a synchronous long‐distance dispersal event. (3rd May 2014) - Nowak, M. D.; Haller, B. C.; Yoder, A. D.
Abstract The stochastic process of long‐distance dispersal is the exclusive means by which plants colonize oceanic islands. Baker's rule posits that self‐incompatible plant lineages are unlikely to successfully colonize oceanic islands because they must achieve a coordinated long‐distance dispersal of sufficiently numerous individuals to establish an outcrossing founder population. Here, we show for the first time that Mauritian Coffea species are self‐incompatible and thus represent an exception to Baker's rule. The genus Coffea (Rubiaceae) is composed of approximately 124 species with a paleotropical distribution. Phylogenetic evidence strongly supports a single colonization of the oceanic island of Mauritius from either Madagascar or Africa. We employ Bayesian divergence time analyses to show that the colonization of Mauritius was not a recent event. We genotype S‐RNase alleles from Mauritian endemic Coffea, and using S‐allele gene genealogies, we show that the Mauritian allelic diversity is confined to just seven deeply divergent Coffea S‐RNase allelic lineages. Based on these data, we developed an individual‐based model and performed a simulation study to estimate the most likely number of founding individuals involved in the colonization of Mauritius. Our simulations show that to explain the observed S‐RNase allelic diversity, the founding population was likely composed of fewer than 31 seeds that were likely synchronously dispersed from an ancestral mainland species.